Combination Therapy of Prednisone, Azathioprine, and Hydroxychloroquine in Patient with Dermatomyositis - Swanenghyun, Garnis; Yuniaswan, Anggun Putri (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
manifestations of inflammatory myopathy accompanied by cutaneous involvement. In patients with cutaneous DM, for the first line of therapy can be given photoprotection, topical steroids, Hydoroxychloroquin (HCQ) or Chloroquine and Quinacrine, while the gold standard in DM myopathy is systemic corticosteroids. Inadequate therapeutic regimens can result in morbidity or complications, especially calcinosis. Case Presentation: A 29-year-old woman had reddish spots on her face and hands accompanied by pain in her hands, hips, knees and elbows making it difficult for the patient to walk. Found it exists Heliotrop sign, Gottron papule and Gottron sign. The main aim of providing therapy to DM patients is to reduce inflammation, such as minimizing symptoms, especially those related to muscle weakness and improving the patient's quality of life. Glucocorticoids remain the first line therapy option for DM with the choice of oral prednisone 1mg/kgBW/day. Meanwhile, moderate to severe DM specifically should be treated with a combination which contains steroids and immunosuppressants, such as Methotrexate (MTX), Azathioprine (AZA), or Mycophenolate Mofetil (MMF). The therapy regimen must be given appropriately and adequately to minimize the occurrence of complications. Conclusion: A combination of Prednisone, Azathioprine, andHydoroxychloroquin is effective as a therapy for Dermatomyositis. This can be proven by an increase in muscle strength and the red spots disappearing in this patient.